Development of English Board Learning Media to Increase Learning Motivation in English Subjects in Grade 3 of Elementary Madrasah - Novitaningrum, Diah Tri; Alfiyah, Hanik Yuni; Sa’diyah, Siti Halimatus (Prodi PGMI STAI At-Tahdzib Ngoro Jombang, 2024)
Students are less motivated to follow the English learning process. The methods and approaches used by teachers are less interesting to students, still centered on the teacher. This study developed English board learning media, and to increase student enthusiasm and make it easier for teachers to transfer knowledge to students. English Board is expected to be fun, interesting, and motivating, and not make students bored when participating in English learning activities. The